2019
DOI: 10.1038/s41598-019-55290-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the intestinal microbiome of healthy children and patients with newly diagnosed Crohn’s disease

Abstract: The aetiology of inflammatory bowel diseases (IBD) seems to be strongly connected to changes in the enteral microbiome. The dysbiosis pattern seen in Crohn’s disease (CD) differs among published studies depending on patients’ age, disease phenotype and microbiome research methods. The aims was to investigate microbiome in treatment-naive paediatric patients to get an insight into its structure at the early stage of the disease in comparison to healthy. Stool samples were obtained from controls and newly diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 43 publications
10
83
0
5
Order By: Relevance
“…51 Dialister species are known to have reduced abundance in adult and paediatric CD patients relative to healthy controls. 52,53 Interestingly Dialister also has higher relative abundance in CD patients who are in remission following ileocaecal resection than those who have post-operative recurrence. 54 It is possible that Dialister, with its bimodal abundance distribution, acts as a biomarker of mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…51 Dialister species are known to have reduced abundance in adult and paediatric CD patients relative to healthy controls. 52,53 Interestingly Dialister also has higher relative abundance in CD patients who are in remission following ileocaecal resection than those who have post-operative recurrence. 54 It is possible that Dialister, with its bimodal abundance distribution, acts as a biomarker of mucosal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, pediatric patients with IBD are observed to have an imbalance in their gut microbiome, referred to as dysbiosis [ 83 ]. Several studies have demonstrated that a reduction in microbial diversity and richness is a key feature of both pediatric and adult IBD [ 81 , 84 , 85 , 86 ]. Studies have also shown that pediatric patients with IBD exhibit a significantly decreased abundance of Firmicutes and Bacteroidetes while displaying a significant expansion of Proteobacteria [ 84 , 87 , 88 , 89 , 90 , 91 ].…”
Section: Inflammatory Bowel Disease and The Gut Microbiomementioning
confidence: 99%
“…Within the phylum Actinobacteria, a decrease in the abundance of Bifidobacterium spp. has been observed in pediatric IBD patients when compared to healthy controls [ 86 , 88 ]. Indeed, Bifidobacterium spp.…”
Section: Inflammatory Bowel Disease and The Gut Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…Fusobacterium [31], whereas the Ulcerative Colitis has the same pattern of GM, but with a more predominant decrease of Fusobacterium [32]. On the one hand, there are other contexts, such as Henoch-Schönlein purpura where the keystone is the detection in the Enterococcus who play a role in the pro-inflammatory state [33].…”
Section: Discussionmentioning
confidence: 99%